2018
DOI: 10.1002/mnfr.201800716
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a TLR2 Inhibiting Wheat Hydrolysate

Abstract: Scope Wheat hydrolysates are used in medical nutrition to provide undernourished patients a readily digestible protein source, for instance to recover from chemotherapy‐induced intestinal mucosal inflammation. Since many hydrolysates of different sources can modulate the immune system, likely via Toll‐like receptors (TLRs), it is hypothesized that also wheat hydrolysates might interact with TLR signaling, which could be a way to prevent intestinal inflammation and damage. Methods an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
(94 reference statements)
0
4
0
Order By: Relevance
“…After optimization by comparing concentrations of 2, 5, and 10 mg mL −1 in a pilot study, a slight, gradual increasing effect was observed when the concentration increased. As 2 mg mL −1 elicited a response allowing quantification in time, 2 mg mL −1 was finally chosen …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After optimization by comparing concentrations of 2, 5, and 10 mg mL −1 in a pilot study, a slight, gradual increasing effect was observed when the concentration increased. As 2 mg mL −1 elicited a response allowing quantification in time, 2 mg mL −1 was finally chosen …”
Section: Methodsmentioning
confidence: 99%
“…As 2 mg mL −1 elicited a response allowing quantification in time, 2 mg mL −1 was finally chosen. [24,25]…”
Section: Carbohydratesmentioning
confidence: 99%
“…As already explained in Section 3, inhibition of TLR‐2 signaling can be a method of preventing the pathogenesis of COVID‐19. Wheat hydrolysate, having the peptide WQIPEQSR was found to inhibit TLR‐2 signaling, and even attenuate the signaling of TLR‐2|TLR‐1 and TLR‐2|TLR‐6 dimers (Kiewiet et al., 2018). This further adds to the prospective benefits, which bioactive peptides can possess.…”
Section: Immunity Boosting Nutraceuticalsmentioning
confidence: 99%
“…It is very likely that beyond our predicted peptides a larger number of peptides contributed to physiological effects of the bioactive protein hydrolysates. 29…”
Section: From In Silico Peptides To a Nutritional Productmentioning
confidence: 99%